2016
DOI: 10.1113/jp272599
|View full text |Cite
|
Sign up to set email alerts
|

Secondary hyperalgesia is mediated by heat‐insensitive A‐fibre nociceptors

Abstract: Secondary hyperalgesia refers to the increase in sensitivity to mechanical nociceptive stimuli delivered outside the area of tissue injury. Previous studies have suggested that secondary hyperalgesia is mediated by a specific class of myelinated nociceptors: slowly adapting A-fibre mechano- and heat-sensitive (AMH) type I nociceptors. Here, we tested this hypothesis by examining whether long-lasting heat stimuli, which are known to activate AMH-type I nociceptors, elicit enhanced responses when delivered to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 31 publications
(48 reference statements)
3
28
1
Order By: Relevance
“…All stimuli were clearly perceived, but the intensity of the elicited sensations was greater for large vs. small decreases in skin temperature, as well as for stimulation using a large vs. small stimulation surface. Previous studies have shown that cool perception is abolished during the presence of an A-fibre nerve compression block (Oliveiro et al, 2005; van den Broeke et al, 2016), which strongly suggests that cool sensation is mediated by cool-sensitive A-fibres. Moreover, electrophysiological recordings of single nerve fibers in primates have identified a subpopulation of cool-sensitive A-fibers that (1) discharge rapidly at the onset of cooling the skin, (2) respond more strongly for fast vs. slow rates of cooling, (3) do not respond or respond minimally to mechanical stimuli and (4) have their ongoing activity suppressed by rapid warming of the skin (Darian-Smith et al, 1973; Dubner et al, 1975; Kenshalo and Duclaux, 1977).…”
Section: Discussionmentioning
confidence: 89%
“…All stimuli were clearly perceived, but the intensity of the elicited sensations was greater for large vs. small decreases in skin temperature, as well as for stimulation using a large vs. small stimulation surface. Previous studies have shown that cool perception is abolished during the presence of an A-fibre nerve compression block (Oliveiro et al, 2005; van den Broeke et al, 2016), which strongly suggests that cool sensation is mediated by cool-sensitive A-fibres. Moreover, electrophysiological recordings of single nerve fibers in primates have identified a subpopulation of cool-sensitive A-fibers that (1) discharge rapidly at the onset of cooling the skin, (2) respond more strongly for fast vs. slow rates of cooling, (3) do not respond or respond minimally to mechanical stimuli and (4) have their ongoing activity suppressed by rapid warming of the skin (Darian-Smith et al, 1973; Dubner et al, 1975; Kenshalo and Duclaux, 1977).…”
Section: Discussionmentioning
confidence: 89%
“…; Van den Broeke et al . ). Studies have suggested that this heterotopic increase of mechanical pinprick sensitivity is abolished during A‐fibre nerve conduction blockade (Ziegler et al .…”
Section: Introductionmentioning
confidence: 97%
“…This dichotomy had been supported by several additional converging lines of evidence, including selective nerve blocks in healthy subjects and electrophysiological recordings from nociceptive afferents and nociceptive spinal neurons in monkeys (for discussion see: Van den Broeke et al . ; Henrich et al . ).…”
Section: Pain Amplification In Neurogenic Hyperalgesiamentioning
confidence: 99%
“…In this issue of The Journal of Physiology , André Mouraux and colleagues (Van den Broeke et al . ) have now investigated which type of A‐fibre nociceptor mediates the hypersensitivity to pinprick pain surrounding a site of HFS. Based on previous publications, there were two candidates left: mechano‐heat sensitive A‐fibre nociceptors (type I AMH) or heat‐insensitive high‐threshold mechanoreceptors (HTM).…”
Section: Pain Amplification In Neurogenic Hyperalgesiamentioning
confidence: 99%